FAKTOR-FAKTOR YANG MEMPENGARUHI DAYA TARIK WISATAWAN UNTUK MENGUNJUNGI CURUG CIGENTIS KECAMATAN TEGALWARU KABUPATEN KARAWANG - Rianto Rianto; Prayogo Susanto (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2020)
The purpose of this study was to determine what factors influence the decision to visit tourist destinations, especially Curug Cigentis, which is one of the tourist destinations in the Karawang Regency area, which includes factors from the aspect of tourist attraction (market share, attractions, infrastructure, accessibility, facilities and infrastructure). tourism services and institutional elements). Tourist attraction is everything with uniqueness and high value, which is the basis for tourists to come to a certain area. This research is expected to be able to provide information for the management of Curug Cigentis about tourist attraction factors, so that it can be implemented in determining the strategy that must be determined by the manager of Curug Cigentis to increase tourist attraction. Data was collected through documentation and questionnaire methods (questionnaire). The sample in this study were 100 people who had visited Curug Cigentis. In this study, the authors use non-probability sampling with the sampling technique used is incidental sampling, which is a technique for determining the sample based on chance and is suitable as a data source.